Load frequency control of thermal system under deregulated environment using slime mould algorithm - Sambugari Anil Kumar; M. Siva Sathya Narayana; K. Jithendra Gowd (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper emphasizes the significance of proportional-integral-derivative (PID) controller parameters using a slime mould algorithm (SMA) to reduce load frequency control (LFC) issues in a thermal system in an open market scenario. The SMA is used to solve the parameterization of the PID controller, which was formulated as an optimization problem. The performance of the PID controller parameters improves the dynamic characteristics of the system as frequency in each area, and also deviations in tie line power after sudden load violation. In order to study the efficiency of the proposed method, the system was tested with different power transactions for a small load disturbance and the comparative results were presented. The optimal value of the controller parameters derived from SMA based PID controller is estimated using a finite nonlinear optimization using a performance index based method.